High-latitude environmental change during MIS 9 and 11: biogeochemical evidence from Lake El'gygytgyn, Far East Russia - R. M. D'Anjou; J. H. Wei; I. S. Castañeda; J. Brigham-Grette; S. T. Petsch; D. B. Finkelstein (Climate of the Past, 2013)
Marine isotope stages (MIS) 11 has been proposed as an analog for the present interglacial; however, terrestrial records of this time period are rare. Sediments from Lake El'gygytgyn (67°30' N, 172°5' E) in Far East Russia contain a 3.56 Ma record of climate variability from the Arctic. Here, we present the first terrestrial Arctic reconstruction of environmental and climatic changes from MIS 8 through 12 (289 to 464 ka) using organic geochemical proxies. Terrestrial vegetation changes, as revealed by plant leaf wax (n-alkane) indices and concentrations of arborinol (a biomarker for trees), show increased tree cover around the lake during interglacial periods, with higher concentrations observed during MIS 11 as compared to MIS 9. A similar pattern is also observed in records of aquatic productivity revealed by molecular indicators from dinoflagellates (dinosterol), eustigmatophyte algae (long-chain (C28–C32) 1, 15 n-alkyl diols) in addition to short-chain n-alkanes, where aquatic productivity is highest during MIS 11. Changes recorded in these molecular proxies show a similar structure to relative temperature variability as recorded by the MBT/CBT (Methylation of Branched Tetraether/Cyclization of Branched Tetraether) paleothermometer, based on branched glycerol dialkyl glycerol tetraethers (GDGTs). Additionally, relative MBT/CBT temperature changes generally track pollen and diatom δ18O temperature estimates, compiled by other studies, which suggest glacial-interglacial temperature changes of ~ 9 to 12 °C. These records of environmental and climatic change indicate Arctic sensitivity to external forcings such as orbital variability and atmospheric greenhouse gas concentrations. Overall, this study indicates that organic geochemical analyses of the Lake El'gygytgyn sediment archive can provide critical insight into the response of lake ecosystems and their sensitivity in high latitude regions.